Self-Powered High-Performance Broadband Heterojunction Photodetector Based on Nitrogen- and Boron-Doped Graphene Oxide - Yildirim, Fatma; Yaman, Mehmet; Yilmaz, Mehmet; Kocyigit, Adem; Aydogan, Sakir (Amer Chemical Soc, 2025)
In this work, B- and N-doped reduced graphene oxide was obtained from Doruk Grafen (Anbiokim, Doruk, Turkey) and a high-performance self-powered rGO(B:N)/n-Si heterojunction photodetector based on rGO(B:N) was successfully fabricated. The obtained materials have been corrected by using Raman and XPS spectroscopy measurements. From these, the characteristic D and G peaks for reduced graphene oxide were clearly observed in the Raman spectrum. Also, the doping elements B and N have been detected in the XPS measurements. The device fabricated on the basis of this material exhibited antisymmetric I-V characteristics in the dark and provided a rectification as high as 3.57 x 10(5) A. Photoelectrical measurements of the rGO(B:N)/n-Si photodetector were performed in visible light and under different wavelengths of 365, 395, 590, and 850 nm. The device was found to give an increasing photocurrent with varying light intensity under visible light. It was also found to give high-performance photodetector characteristics at 365, 395, 590, and 850 nm. The rGO(B:N)/n-Si photodetector exhibited high performance, including an ultrahigh responsivity of 793.6 mA/W (at -1.5 V), a detectivity of 2.15 x 10(12) Jones (at 0.0 V), and a high ON/OFF ratio of over 10(4) under yellow light illumination of 8 mW/cm(2) (at zero bias). For the time-dependent stability measurements of the device, it was observed that the device remained largely stable, even 295 days after its production.
Keywords: rGO(B:N); rGO/n-Si photodetector; broadband; detectivity; ON/OFF ratio